Christian confessions : a historical introduction - Ted A. Campbell (Louisville, Kentucky Westminster John Knox Press, 2005)
Ted Campbell examines, in a comparative framework, the historic teachings of the four major Christian traditions that have shaped our theological heritage - Eastern Orthodoxy, Roman Catholicism. Reformation and Union churches, and Evangelical and Free churches. He provides an extensive overview of each tradition's particular beliefs on religious authority, God and Christ, human nature and salvation, and church, ministry, and the sacraments. He concludes by considering whether a definable core of Christian teachings cuts across denominational and confessional boundaries.
Keywords: Comparative Theology (3GddGghJ GdebGQfs; Christian sects; Theology, Doctrinal; Creeds -- Comparative Theology